PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP KUALITAS TIDUR LANSIA DI WILAYAH DUSUN SIDODADI KABUPATEN NGAWI: - Inggit Zulkharisma Kamto; Erika Dewi Noorratri (Jurnal Ilmu Keperawatan Komunitas, 2022)
health issues among the elderly, one of which is insomnia or sleep disorders. In Indonesia, the prevalence of sleep problems in individuals aged 60 obtained an extremely high number of cases ranging from 67%. Pharmacological and non-pharmacological handling is used to overcome sleep quality. Pharmacological treatment has undesirable side effects result in patient dependence. Meanwhile, non-pharmacological treatment can reduce sleep disruptions through progressive muscle relaxation therapy techniques. Progressive muscle relaxation therapy can enhance feelings of comfort and psychological relaxation by improving sleep quality in older adults. Objective: To determine whether progressive muscle relaxation exercisesaffected enhanced sleep quality in the elderly of Sidodadi Hamlet. Methods:This examination employed a quantitative approach,applying a quasi-experimental design, with a pre-test and post-test, without a control group design. This study utilised a non-probability sampling technique in the shape of purposive and the Wilcoxon test, with comprised 30 elderly sampled.Results: The Wilxocon test obtained results with a p-value of 0,000. Conclusion:Progressive muscle relaxation therapy affected on the sleep quality of the older adults in Sidodadi Hamlet, Ngawi Province. Keyword : eldery, sleep quality, progressive muscle relaxation